2014
DOI: 10.1088/0004-6256/148/6/122
|View full text |Cite
|
Sign up to set email alerts
|

Ysovar: Mid-Infrared Variability in the Star-Forming Region Lynds 1688

Abstract: The emission from young stellar objects (YSOs) in the mid-IR is dominated by the inner rim of their circumstellar disks. We present an IR-monitoring survey of ∼ 800 objects in the direction of the Lynds 1688 (L1688) star forming region over four visibility windows spanning 1.6 years using the Spitzer space telescope in its warm mission phase. Among all lightcurves, 57 sources are cluster members identified based on their spectral-energy distribution and X-ray emission. Almost all cluster members show significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 105 publications
9
65
0
Order By: Relevance
“…The number of observations given in column two is not the same for all sources in a field due to edge effects or artifacts in the image unrelated to deriving accurate positional information. The last column notes comparisons to previous variability studies by Alves de Oliveira & Casali (2008), Parks et al (2014), and Günther et al (2014). We note that the most extensive of these was by Parks et al, who utilized nearly daily observations over a 2.5 year period from the 2MASS survey (Cutri et al 2003).…”
Section: Confirmed and Possible New Variablesmentioning
confidence: 88%
“…The number of observations given in column two is not the same for all sources in a field due to edge effects or artifacts in the image unrelated to deriving accurate positional information. The last column notes comparisons to previous variability studies by Alves de Oliveira & Casali (2008), Parks et al (2014), and Günther et al (2014). We note that the most extensive of these was by Parks et al, who utilized nearly daily observations over a 2.5 year period from the 2MASS survey (Cutri et al 2003).…”
Section: Confirmed and Possible New Variablesmentioning
confidence: 88%
“…In addition, the disk is detected at 70 µm with Herschel/PACS . It was listed as a long timescale near-infrared variable by Parks et al (2014), while Günther et al (2014) detected ∼20% variations in the mid-infrared with Spitzer.…”
Section: Appendixmentioning
confidence: 99%
“…p CHXR 37: 0 079 (13 au) binary (Lafrenière et al 2008 Table 3). In particular, the YSOVAR survey, with its Spitzer observations of IRAS:20050 +2720 , NGC 1333 (Rebull et al 2015), the ONC (Morales-Calderón et al 2011), L1688 (Günther et al 2014), and GGD 12-15 , finds that 60%-85% of YSOs with an infrared excess are variable. Studies of IC 348 , NGC 2264 , and the Orion molecular cloud (Megeath et al 2012) have found similar results.…”
Section: Finding Variable Starsmentioning
confidence: 99%